From in the of the Judicial System in Turkestan - Abdujalilovna, Ismoilova Dilfuzaxon (European Journal of Life Safety and Stability (2660-9630), 2021)
The article provides information about the judicial system of Turkestan, its structure, types of courts. There is information about the activities of positions (judges) in the judicial system, requirements for the position of a judge. It also covers the study of the regional judicial system of the Russian Empire, its policy towards it, changes in the courts and the attitude of the local population towards them.